Athenry Castle, east interior wall of hall, window, jamb and arch - O'Donovan, Danielle (My University, 2008)
Angle shaft of splayed window jamb. Moulding, from arris comprises: roll flanked by quarter hollows.
East window
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Medieval; roll moldings; moldings, hollow